Trust aftereffect: adaptation to own or other race faces biases subsequent trust judgements - Ong, Tulip Yu Lay (Nanyang Technological University, 2024)
Trust plays an important role in maintaining good inter-racial relationships. Hence, understanding what the factors affect trust judgement is crucial. In our daily life, we are exposed to many faces. Literature on the multi-dimensional face space and adaptation suggest that the type of faces one is exposed to could affect people’s trust judgement. Studies on adaptation found that adapting to one’s own or other race face can bias the subsequent race perception. However, whether the same aftereffect is present in trust adaptation remains unaddressed. Using the adaptation paradigm, thirty-five participants were instructed to make a trust judgement about a face after adapting to a Chinese (own race) or Caucasian (other race) face. Results from the trust adaptation task showed that participants’ trust judgements were biased by the adaptors that preceded them: after adapting to a Chinese face (own race), participants trusted all the Chinese-Caucasian morphed faces less while after adapting to a Caucasian face (other race), participants trusted the same set of faces more. This suggests that a trust aftereffect was indeed present after adapting to an own or other race face. The findings imply that people’s tendency to trust their own race more than other races could be due to their over exposure to own race faces and limited exposure to other race faces. The fact that a mere exposure to other or own race faces could affect people’s trust perception also provides much practical implications for policymakers and campaigners who are trying to improve inter-racial relationships.